Patients with suspected benign tumors and glial fibrillary acidic protein autoantibody: an analysis of five cases. (2nd December 2019) - Huang, Qingmei; Yang, Huacai; Liu, Tianni; Xu, Huiming; Chen, Baikeng; Liu, Si; Li, Wenfeng; Long, Youming; Gao, Cong
Abstract: Aim: To investigate the clinical features of five glial fibrillary acidic protein (GFAP) antibody positive patients with suspected benign tumors and explore its underlying pathogenesis. Materials and methods: Overall, 1018 serum and cerebrospinal fluid (CSF) samples were tested by indirect immunofluorescence assay and data from five patients with suspected tumors and positive for GFAP autoantibody in the CSF were analyzed retrospectively. Results: The positive rate of GFAP antibody in the serum and CSF was 3.93% by indirect immunofluorescence assay. Tumors were diagnosed before or after neurologic onset in 5 of 40 patients (12.5%) and no deterioration of the tumors was found during the long-term follow-up. Of the five patients, one patient suffered a thyroid nodule, one patient had a small nodule in the left lung, two patients suffered meningiomas, and one patient had a suspicious eosinophilic granuloma. Conclusion: GFAP autoimmunity may be a paraneoplastic immune response with a low frequency of tumor in Chinese patients with GFAP astrocytopathy.